Pandemic and income inequality increase in Brazil: Challenges to the Unified Social Assistance System (SUAS): Pandemic and income inequality increase in Brazil: Challenges to the Unified Social Assistance System (SUAS) - Pereira Lisboa, Camila (Revista Desenvolvimento Social, 2022)
This article will contribute to discuss the impacts of COVID-19 on Brazilian social inequality and some increased challenges to the Unified Social Assistance System (SUAS) in the face of this. For that, we mention some inequalities existing in the country, and how they increased with the arrival of the pandemic. To help us to understand how SUAS was affected, some federal government regulations aimed at this system are cited, published in the first year of the pandemic, in 2020, on the SUAS Network blog. Finally, it is concluded that such regulations seek to offer palliatives for the increase in poverty and income inequality in the country in the face of the coronavirus, but they do not aim to offer long-term solutions to these problems.